Exploring of Online Learning Using Youtube in English Vocabulary During The Covid-19 Pandemic - Rini Yulianti Putri (Jurnal Inovasi Penelitian dan Pengabdian Masyarakat, 2022)
Since the Covid-19 pandemic, all activities have been hampered, from work to school which hampers the conventional learning process or face-to-face learning. The objectives of this research aims to discover the positive things taken from YouTube for online English learning media daring this covid-19 pandemic. This research is qualitative research in which the author uses the literature study observations taken from previous researchers. Currently, schools have implemented online learning, where teachers are required to use a monotonous lecture method. This is one of the problems that will cause students to be unenthusiastic and unfocused when studying. Therefore, this study shows that utilizing Youtube media can improve vocabulary and student understanding in English lessons, increasing student achievement. However, there must be disadvantages every time there are advantages: the lack of optimal supervision of students, poor signal or internet network, and high quotas are the obstacles to using YouTube as a learning medium